Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1055/s-0038-1647300
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Antibodies to Recombinant Human Tissue-Type Plasminogen Activator in Treated Patients

Abstract: SummarySera from over 1,600 patients who received recombinant human tissue plasminogen activator (rt-PA) during clinical trials were assessed for the presence of antibodies to this therapeutic agent. The rt-PA was administered by a variety of dosage regimens for several different indications. Two different forms of rt-PA were used; one was a predominantly two chain form, and the other was a predominantly one chain form. A sensitive radioimmunoprecipitation assay was used to measure antibodies to rt-PA in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…Animal models have demonstrated the formation of antibodies against rtPA [12, 13]. However, development of these antibodies in humans is unusual [14] and there are only occasional reports of IV rtPA-related anaphylactic reactions in “real-life” clinical practice [15]. Moreover, no anaphylactic reactions have been described among any of the 13 cases of repeated IV thrombolysis for ischemic stroke reported up to date (including ours).…”
Section: Clinical Case and Discussionmentioning
confidence: 93%
“…Animal models have demonstrated the formation of antibodies against rtPA [12, 13]. However, development of these antibodies in humans is unusual [14] and there are only occasional reports of IV rtPA-related anaphylactic reactions in “real-life” clinical practice [15]. Moreover, no anaphylactic reactions have been described among any of the 13 cases of repeated IV thrombolysis for ischemic stroke reported up to date (including ours).…”
Section: Clinical Case and Discussionmentioning
confidence: 93%
“…5 Several studies investigated the development of antibodies against rt-PA after treatment for a variety of cardiac and noncardiac indications in humans. 3,4 Reed et al screened 1.686 patients after rt-PA administration and identified only 3 patients (Ͻ0.01%) who developed significant titers of antibodies. 3 Conversely, Cugno et al showed significantly increased titers in 14% of cardiac patients after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Reed et al screened 1.686 patients after rt-PA administration and identified only 3 patients (Ͻ0.01%) who developed significant titers of antibodies. 3 Conversely, Cugno et al showed significantly increased titers in 14% of cardiac patients after treatment. 4 Hence, the overall incidence of post-treatment antibodies against rt-PA is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations